Le secteur sauvegardé, un outil indispensable mais insuffisant pour le développement d’un centre-ville historique - Emmanuelle Gillet Lorenzi (Projets de Paysage)
With the Malraux law in France, urban centres have acquired an historical as well as a functional value. The protected area thus makes it possible to develop a territorial strategy of protection and management of the landscape in the sense of Article 1 of the Convention of Florence. However, this strategy cannot be truly effective if it is not an integral part of the planning policy of the urban area concerned. This article raises the question of the reality and the challenges of the complementarity between heritage and urban development. It shows how this complementarity is possible today, it then analyses how a territory may address the heritage question by evolving from protecting what exists towards a manner of using the landscape. Finally it presents solutions intended to deal with the degradation of the landscape.